How to Watch the Story of Film Adaptation. Cortázar, Antonioni, Blow-Up - Cisneros, James (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2003)
A brief heuristic survey of research on the adaptation of literature to film shows that it has consistently given priority to the narrative of the classical cinema, effacing the media's respective material support as well as its place in a history of visual regimes. Instead of following this institutional comparative paradigm, with its implications for agency and reception, this article develops an approach to adaptation that places the media's technologies at the center of the storytelling process. A case study of Cortázar's short story “Las Babas del Diablo” and Antonioni's film Blow-Up, it focuses on how each of these nearly theoretical texts outlines the kind of story that pushes its own discursive processes into the foreground.